Religious and sacred art: Recent psychological perspectives - Schieppati, Sara Valentina; Di Dio, Cinzia; Gilli, Gabriella (Ricerche di Psicologia - Open Access, 2022)
The psychology of art has had an enormous development since the middle of the last century; however, no much work has been done in association with religious and sacred art. This paper aims to provide a brief history of the use of images in the three great monotheistic religions, i.e., Judaism, Christianity, and Islam. All three religions have been influenced by the commandment (Exodus, 20:4), which prohibits idolatry. Nevertheless, when it comes to the use of images with religious content, the commandment is interpreted differently by the three. If in Judaism and Islam the use of images is not particularly widespread and is bound to precise conditions, in Christianity a strong relationship with the visual arts has developed, at least until the Reformation. After this split, the use of images was only encouraged by the Catholic Church even though, with the Enlightenment, religious and sacred art suffered a decline even in Catholic culture. It was not until the twentieth and twenty-first centuries that the Catholic Church returned to support and encourage art in the religious context. It will then be necessary to distinguish between religious art and sacred art because they serve different functions. Precisely because it is a field in which deepening is possible, it could be very interesting for the psychology of art to study the perception of religious and sacred images, for example investigating constructs associated with the perception of vitality and aesthetic judgment.